TRANSFORMASI PEMBELAJARAN BERBASIS TEKNOLOGI: MEMADUKAN PEMBELAJARAN KLASIKAL DAN DIGITAL PADA PROGRAM STUDI MANAJEMEN PENDIDIKAN FIP UNESA - Poltjes Pattipeilohy; Karwanto Karwanto; Supriyanto Supriyanto; Windasari Windasari; Aditya Chandra Setiawan; Kaniati Amalia; Ahmad Abdullah Zawawi; Johan Pattiasina; Sindy Sindy (Universitas Nusa Cendana, 2025)
The transformation of learning through the integration of classical and digital methods is a necessity in responding to the challenges of 21st century education. This study aims to examine the implementation and impact of the blended learning model in the FIP UNESA Education Management Study Program, as well as formulate an ideal integrated learning model. This study uses a descriptive qualitative approach with data collection techniques through questionnaires, in-depth interviews, and document analysis. The data was analyzed thematically by linking the findings with education management theory and learning technology. The results show that the use of technology such as LMS, collaborative applications, and interactive media has increased the accessibility and flexibility of student learning. However, challenges such as limited infrastructure, lecturer readiness, and digital literacy gap are still obstacles. The research recommends an interaction-based blended learning model supported by infrastructure support, lecturer capacity building, and varied and relevant digital content, to ensure the quality and sustainability of learning in higher education environments.